2001
DOI: 10.1097/00007890-200112270-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ????- And ????-T Cells in Allogeneic Donor Marrow on Engraftment, Chimerism, and Graft-Versus-Host Disease1

Abstract: These data demonstrate that depletion of T cells from rat marrow does not impair engraftment of HSCs, indirectly supporting the existence of FCs in rat marrow. Moreover, donor alphabeta- and gammadelta-TCR(+) T cells contribute to GVHD in a nonredundant fashion, although alphabeta-TCR(+) T cells are more potent as the effector cells. Finally, the level of donor chimerism is influenced by the composition of the graft, because recipients of marrow that contain alphabeta-TCR(+) T cells exhibited significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
0
24
1
Order By: Relevance
“…However, this result arose not only from the adopted immunosuppressive protocol but also from the dosage of transplanted BMC. In experimental studies where GVHD developed in the comparable rat model, the number of transplanted allogenic BMC was higher than that in our study: GVHD was induced after transplantation of 100 Â 10 6 T-cell depleted BMC into total-body irradiated rats, 23 whereas in our model the highest dosage of BMC was 70 Â 10 6 and animals did not undergo myeloablative therapy. Moreover, in experimental studies in which the effect of different doses of tacrolimus was used to prevent GVHD after whole-organ or cell suspension transplantation, the dosage of BMC was significantly higher than in our study, specifically 2.5 Â 10 8 cells.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, this result arose not only from the adopted immunosuppressive protocol but also from the dosage of transplanted BMC. In experimental studies where GVHD developed in the comparable rat model, the number of transplanted allogenic BMC was higher than that in our study: GVHD was induced after transplantation of 100 Â 10 6 T-cell depleted BMC into total-body irradiated rats, 23 whereas in our model the highest dosage of BMC was 70 Â 10 6 and animals did not undergo myeloablative therapy. Moreover, in experimental studies in which the effect of different doses of tacrolimus was used to prevent GVHD after whole-organ or cell suspension transplantation, the dosage of BMC was significantly higher than in our study, specifically 2.5 Â 10 8 cells.…”
Section: Discussioncontrasting
confidence: 62%
“…However, increase in the intensity of conditioning regimens and aggressive T-cell depletion also promotes the occurrence of GVHD. 7,23 Conversely, in the rat model persistence of a CD8 þ / CD3 þ /TCR-population of T cells, characterized as facilitating cells, increases the engraftment of donor cells and minimizes GVHD. 23 The facilitating role of CD8 þ cells has also been demonstrated in a murine model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21] One study reported that a clonal population of ␥␦ T cells can induce lethal GVHD, 17 whereas Drobyski and Majewski 20 and Drobyski et al 21 demonstrated that donor ␥␦ T cells alone do not cause acute GVHD. Coadministration of ␥␦ T cells and ␣␤ T cells exacerbated GVHD when compared with ␣␤ T cells alone, suggesting that donor ␥␦ T cells could contribute to GVHD but required the presence of ␣␤ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have focused on the role played by donor ␥␦ T cells in GVHD, [15][16][17][18][19][20][21] but the role of host ␥␦ T cells is not known. Using several mouse models, we have found that host ␥␦ T cells exacerbate acute GVHD by enhancing the allostimulatory capacity of host APCs.…”
Section: Introductionmentioning
confidence: 99%